What professional factors do teachers identify as stressful in an international school? - Hu, Shanshan (2016)
In this study, I aimed to identify the professional factors that cause teachers to feel stressed working in an international school in Italy and whether are those factors are related to the international context of the school. I carried out semi-structured interviews with six classroom teachers who currently work at the school. Five out of the six teachers reported that working in this international school was either mildly stressful or moderately stressful, with one teacher reporting that it is very stressful. The three main sources of stress identified were: the workload; time limitations; and the lack of resources. Teachers all revealed from their own teaching experience that if they feel stressed, it does affect them personally and professionally. Three teachers even described their experiences of near 'burnout' in their previous schools in the UK. Teachers also gave some productive suggestions for the school to help to prevent and reduce stress. These findings are mostly in line with those reported in previous research, whilst there are some differences according to the international school context.